THE EFFECTS OF A DECOMPRESSION ON SEISMIC PARAMETER PROFILES IN A GAS-CHARGED MAGMA - Sturton S.; Neuberg J. (My University, 2003)
Seismic velocities in a gas-charged magma vary with depth and time. Relationships between pressure, density, exsolved gas content, and seismic velocity are derived and used in conjunction with expressions describing diffusive bubble growth to find a series of velocity profiles which depend on time. An equilibrium solution is obtained by considering a column of magma in which the gas distribution corresponds to the magmastatic pressure profile with depth. Decompression events of various sizes are simulated, and the resulting disequilibrium between the gas pressure and magmastatic pressure leads to bubble growth and therefore to a change of seismic velocity and density with time. Bubble growth stops when the system reaches a new equilibrium. The corresponding volume increase is accommodated by accelerating the magma column upwards and an extrusion of lava. A timescale for the system to return to equilibrium can be obtained. The effect of changes in magma viscosity and bubble number density is examined.